2017
DOI: 10.1038/s41590-017-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNF2 inhibits interferon function by promoting K33-linked STAT1 disassociation from DNA

Abstract: Prolonged activation of interferon-STAT1 signaling is closely related to inflammatory autoimmune disorders, and therefore the identification of negative regulators of these pathways is important. Through high-content screening of 115 mouse RING-domain E3 ligases, we identified the E3 ubiquitin ligase RNF2 as a potent inhibitor of interferon-dependent antiviral responses. RNF2 deficiency substantially enhanced interferon-stimulated gene (ISG) expression and antiviral responses. Mechanistically, nuclear RNF2 dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…A recent study revealed that nuclear RNF2 ubiquitin ligase inhibits the type I IFN response. Nuclear RNF2 directly binds to STAT1 after IFN stimulation, promoting K33‐linked ubiquitination within the DNA‐binding domain (K379) of STAT1 and thus causing the disassociation of STAT1/STAT2 from DNA . Among the IRFs, IRF2 has been implicated in the suppression of type I IFN signaling.…”
Section: Type I Ifn Response and Its Regulationmentioning
confidence: 99%
“…A recent study revealed that nuclear RNF2 ubiquitin ligase inhibits the type I IFN response. Nuclear RNF2 directly binds to STAT1 after IFN stimulation, promoting K33‐linked ubiquitination within the DNA‐binding domain (K379) of STAT1 and thus causing the disassociation of STAT1/STAT2 from DNA . Among the IRFs, IRF2 has been implicated in the suppression of type I IFN signaling.…”
Section: Type I Ifn Response and Its Regulationmentioning
confidence: 99%
“…1e). A preference was observed for K33-linked chains, a poorly studied linkage type associated with immune responses and secretory pathway trafficking [31][32][33] . Given the overwhelming 60 60 60 60 60 60 60 10 60 min 10 10 10 10 10 10 10 --------M1 K6 K11 K27 K29 K33 K48 ARTICLE roles of K48-and K63-linked chains in pathogen defense and known modulation of these chain types by bacterial effectors 34,35 , we pursued further analysis of chains with these linkages.…”
Section: Resultsmentioning
confidence: 99%
“…It cleaves many, but not all, lysine-linked di-ubiquitin substrates, with strong activity toward K33-linked di-ubiquitin. K33-linked ubiquitin chains have roles in T cell activation, innate immune response, and post-Golgi protein trafficking [31][32][33] . OtDUB could potentially disrupt any or all of these pathways during an Orientia infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research by Liu et al. found that the E3 ubiquitin ligase RNF2 directly binds to STAT1 after IFNs stimulation and promotes K33‐linked polyubiquitination at K379 of STAT1, in addition to facilitating the disassociation of STAT1/STAT2 from DNA and consequently suppressing the inhibition of ISG transcription and antiviral responses …”
Section: K27‐ K29‐ and K33‐linked Polyubiquitination Are Involved Imentioning
confidence: 99%